Design Change Dynamics in Building Project: From Literature Review to A Conceptual Framework Formulation - Boon Hui, Jeffrey Yap; Abdul-Rahman, Hamzah; Chen, Wang (Journal of Surveying, Construction and Property, 2017)
Building construction projects worldwide routinely fail to meet their schedule and cost objectives. This paper focuses on design changes as the principal contributing factor to delay and cost overruns. Substandard project coordination and futile communication management are sustained problems with the construction industry, particularly as to the management of design changes. To rectify the captioned issues, this study is aimed at exploring the underlying causes of design changes, the resulting rework that is damaging to project performance, communication management process and collaboration in a project-based setting through the review of the literature. Qualitative analysis technique using content analysis method was employed to synthesise the literature and establishing relationships based on the key themes identified. A conceptual model for design change management was then formulated to be the notable outcome of this study. The framework describes the importance of applying effective communication process and informed management decision in dealing with design changes. It provides a coherent and holistic view to understand the dynamics of design changes in a building construction project. It aims to address the current methodological gap in construction management research that lacks demonstrable causality. The findings contribute useful starting point for future overrun causation and mitigation studies.